The Content of Anthocyanins and Chalcones in a Decorative Small-Fruited Apple Trees and Hybrids of Apple Trees „Vydubetska Plakucha“ - Levon, Volodymyr; Goncharovska Іnna (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The content of anthocyanins and chalcones in a decorative small-fruited Apple trees and hybrids of Apple trees cultivars of Vydubetska plakucha from the collection of the M.M. Gryshko National Botanical Garden of NAS of Ukraine in the conditions of Northern Forest-Steppe of Ukraine was investigated. The study was conducted during periods of active shoot growth and winter dormancy in connection with the adaptive capacity of plants. In the result of the study it was found that a decorative small-fruited Apple trees, that have purple color of leaves, contain a large number of anthocyanins, which cause the bright color. Based on the results of the analysis was found the highest content of anthocyanins in the cultivar Everest, and the lowest – in the cultivar John. Noted that the content of chalcones of the decorative purple hybrids of Apple trees of Vydubetska plakucha variety doesn’t have such sharp differences as to the content of anthocyanins. This again confirms the fact that the purple color of the shoots is due to anthocyanins. It is also established that between the content of anthocyanins and chalcones in the shoots of Apple hybrids, cultivars of Vydubetska plakucha found a correlation. The correlation coefficient of 0.84. This suggests that anthocyanins and chalcones belong to the stress metabolites, the biosynthesis of which is activating during action on vegetable organism to adverse environmental factors, they can serve as biochemical markers of the level of adaptability of the species to stressful conditions. In addition, the description of the Vydubetska plakucha cultivars and hybrids with its participation in the collection of the M.M. Gryshko National Botanical Garden of NAS of Ukraine.